Intra- and Inter-Rater Agreement between X-Ray Views for Umbilical Catheter Position - Doreswamy, Srinivasa Murthy; Thomas, Sumesh; Dutta, Sourabh (American Journal of Perinatology, 2019)
Objective We determined intra- and inter-rater agreement for umbilical arterial/venous catheter (umbilical arterial catheter [UAC] and umbilical venous catheter [UVC], respectively) positions on supine anteroposterior (AP) and horizontal dorsal decubitus (HDD) X-ray views to determine whether two views are routinely required.Study Design This retrospective study was conducted in McMaster University, Canada. Pairs of AP and HDD radiographs were coded and rated in random sequence by two experienced raters. Primary outcome was intra-rater agreement (κ) between AP and HDD views for UVC catheter tip position. Secondary outcomes included inter-rater κ for UVC position; inter- and intra-rater κ for UAC position, inter- and intra-rater κ for follow-up action. To detect κ of 0.8 (width of 95% confidence interval = 0.1), 138 radiograph pairs were required.Results Intra-rater agreement tended to be higher for UVC versus UAC position (Rater#1: κ = 0.44 vs. 0.16, respectively, p = 0.08; and #2: κ = 0.56 vs. 0.47, respectively, p = 0.5). Inter-rater agreement was higher on AP versus HDD view for UVC position (κ = 0.6 vs. 0.29, respectively, p = 0.03) and action recommended for UVC (κ = 0.61 and 0.19, respectively, p < 0.001).Conclusion AP is superior to HDD view for UVC.
Keywords: neonate; umbilical venous catheter; umbilical arterial catheter; X-ray